Predictors of school affective engagement during elementary school: A systematic review - Ribeiro,Ana Raquel (2019)
School affective engagement has been extensively studied due to its role in students adaptation and success. The present systematic review aims to examine the predictors and associated factors of school affective engagement in elementary school-age children (6-12 years old). This review examined empirical studies published between 1997 and 2017 selected on the basis of pre-defined criteria. Only eight studies were included in this review. The majority of the studies are quantitative and longitudinal presenting an adequate methodological quality. The results indicated a positive association between teacher-student support and students school affective engagement. However, other relational predictors were less studied, specifically, peers and family factors. Concerning individual factors, studies were also limited in scope, but research examining the role of childrens gender suggests that girls have higher levels of school positive affective engagement than boys. The scarcity of studies focused on predictors of school affective engagement during elementary school indicate that more studies on this topic are needed. Methodological constraints of the studies included are identified and suggestions for future research are made to further improve this area of research.